2015
DOI: 10.1213/ane.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Spinal Analgesia for Labor and Delivery

Abstract: The 23-gauge spinal catheter can be used for analgesia for labor. It can also be converted to surgical anesthesia for cesarean deliveries. Further studies are warranted to determine whether the spinal catheter will be a useful addition to the neuraxial techniques available for obstetric anesthesia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…There was no difference in the rate of maternal fever between women with continuous spinal compared to epidural labor analgesia in our study cohort. While the incidence of maternal fever has not previously been compared between women with continuous spinal and epidural labor analgesia, the incidence of maternal fever in our study is similar to the 14.1% rate reported in an observational study of spinal analgesia provided with 23-gauge intrathecal catheters, 19 and to fever rates in patients with epidural catheters. 20 Our study is unique in that we were able to directly compare the rate of maternal fever between women receiving spinal and epidural labor analgesia.…”
Section: Discussionsupporting
confidence: 87%
“…There was no difference in the rate of maternal fever between women with continuous spinal compared to epidural labor analgesia in our study cohort. While the incidence of maternal fever has not previously been compared between women with continuous spinal and epidural labor analgesia, the incidence of maternal fever in our study is similar to the 14.1% rate reported in an observational study of spinal analgesia provided with 23-gauge intrathecal catheters, 19 and to fever rates in patients with epidural catheters. 20 Our study is unique in that we were able to directly compare the rate of maternal fever between women receiving spinal and epidural labor analgesia.…”
Section: Discussionsupporting
confidence: 87%
“…A high rate of PDPH (28%) was also reported, but the rate of epidural blood patch placement was low (6% overall). Much better success was reported by Tao et al using the same system as Alonso, with no reported failures, no reported neurological deficits, and an incidence of PDPH similar to that reported by Arkoosh et al (8.8%) ( 12 ).…”
Section: Historical Perspectivessupporting
confidence: 64%
“…For labor analgesia, bolus doses 10% of epidural dosing and epidural continuous infusion have been suggested by some ( 23 ), but many authors have found that larger doses are required. A 2 ml/h infusion of a commonly used mixture of local anesthetic and fentanyl for epidural infusion (0.1% ropivacaine + fentanyl 2 µg/ml or 0.0625% bupivacaine + fentanyl 2 µg/ml) is a recommended starting regimen ( 12 , 24 ). Since standard epidural catheters can have up to 1 ml of dead space, a priming volume equal to the catheter volume will be required during the initial dose.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…used a mean (SD) dose of 8.2 (3.6) mg bupivacaine using continuous spinal anaesthesia in an observational study of 92 patients undergoing caesarean section . Continuous intrathecal infusions for labour or caesarean section have been used, where bupivacaine 0.5% is given to a maximum of 25 mg with adjuvant fentanyl . Intrathecal catheters may be ideal therefore for patients with suspected local anaesthetic resistance, allowing repeat doses if the initial dose proves inadequate or of short duration.…”
Section: Discussionmentioning
confidence: 99%